2007
DOI: 10.1002/ijc.22635
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide use and colorectal cancer risk in the agricultural health study

Abstract: We investigated the relationship between agricultural pesticides and colorectal cancer incidence in the Agricultural Health Study. A total of 56,813 pesticide applicators with no prior history of colorectal cancer were included in this analysis. Detailed pesticide exposure and other information were obtained from self-administered questionnaires completed at the time of enrollment (1993)(1994)(1995)(1996)(1997). Cancer incidence was determined through populationbased cancer registries from enrollment through D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
92
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 62 publications
3
92
1
3
Order By: Relevance
“…In a recent publication on the Agricultural Health study (study period from enrollment through 2002, i.e., 7.3 years) chlorpyrifos use showed a significant exposure response trend for rectal cancer, rising to a 2.5-and 2.7-fold increase in risk in the 2 highest exposure categories, while no increase was seen with colon cancer (Lee et al, 2007). These associations between chlorpyrifos and lung and rectal cancer were unexpected in view of the absence of an increased incidence of intestinal or other tumors in animal studies, and the authors conclude that their findings should therefore be interpreted cautiously.…”
Section: Iiib2 Carcinogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent publication on the Agricultural Health study (study period from enrollment through 2002, i.e., 7.3 years) chlorpyrifos use showed a significant exposure response trend for rectal cancer, rising to a 2.5-and 2.7-fold increase in risk in the 2 highest exposure categories, while no increase was seen with colon cancer (Lee et al, 2007). These associations between chlorpyrifos and lung and rectal cancer were unexpected in view of the absence of an increased incidence of intestinal or other tumors in animal studies, and the authors conclude that their findings should therefore be interpreted cautiously.…”
Section: Iiib2 Carcinogenicitymentioning
confidence: 99%
“…These associations between chlorpyrifos and lung and rectal cancer were unexpected in view of the absence of an increased incidence of intestinal or other tumors in animal studies, and the authors conclude that their findings should therefore be interpreted cautiously. Indeed, the positive association is based on small numbers of cases, i.e., an excess of less than 10 cases in the 2 highest exposure groups in the study of Lee et al (2007). Additional uncertainty arises from the limitations in exposure assessment, which is estimated from information recalled by surrogate respondents.…”
Section: Iiib2 Carcinogenicitymentioning
confidence: 99%
“…In previous epidemiologic reports from the Agricultural Health Study (AHS) of specific cancer sites, terbufos use was not associated with cancers of the prostate (7), lung (8), breast (9), colon and rectum (10) or pancreas (11); other cancer sites have not been examined. However, several OPs, including chlorpyrifos (12), diazinon (13), and fonofos (14), have been associated with select cancers in the AHS.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to be possessed genotoxicity and mutagenicity against Drosophila melanogaster (Gupta et al, 2010), rat tissues (Ojiha et al, 2011), mouse lymphocytes (Cui et al, 2011). Epidemiological studies have found some evidence of an association between chlorpyrifos exposure and some cancers (Karunanayake et al, 2012;Waddell et al, 2001;Lee et al, 2007). Immunotoxicity of chlorpyrifos has been shown by Thrasher et al (1993), Gotoh et al (2001), Galloway and Handy (2003).…”
Section: Introductionmentioning
confidence: 99%